Agreement of Bioreactance Cardiac Output Monitoring With Thermodilution in Healthy Standing Horses - Hopster, Klaus; Hurcombe, Samuel D. A. (Frontiers in Veterinary Science, 2021)
Bioreactance is the continuous analysis of transthoracic voltage variation in response to an applied high frequency transthoracic current and was recently introduced for noninvasive cardiac output measurement (NICOM). We evaluated NICOM compared to thermodilution (TD) in adult horses. Six healthy horses were used for this prospective, blinded, experimental study. Cardiac output (CO) measurements were performed simultaneously using TD and the bioreactance method. Different cardiac output scenarios were established using xylazine (0.5 mg/kg IV) and dobutamine (1.5 - 3 mcg/kg/min). Statistical analysis was performed using regression analysis, Pearson correlation and Bland Altman. The TD-based CO and NICOM values were highly correlated for low, normal and high CO values with an overall correlation coefficient of r2 = 0.978 (p<0.001). The linear regression calculated a relationship between NICOM and TDCO of Y = 0.4874 ⋅ X + 0.5936. For the corrected Bland Altman agreement, the mean bias and lower/upper limits of agreement were -0.26 and -3.88 to 3.41 liters per minute, respectively. Compared to TD, bioreactance- based NICOM showed good accuracy at induced low, normal and high CO states in normal horses. Future studies performed under more clinical conditions will show if this monitor can help to assess hemodynamic status and guide therapy in horses in ICU settings and under general anesthesia.